Discrete approximations for strict convex continuous time problems and duality - Andreani, R.; Gonçalves, P. S. [UNESP]; Silva, G. N. [UNESP] (Elsevier, 2004)
We propose a discrete approximation scheme to a class of Linear Quadratic Continuous Time Problems. It is shown, under positiveness of the matrix in the integral cost, that optimal solutions of the discrete problems provide a sequence of bounded variation functions which converges almost everywhere to the unique optimal solution. Furthermore, the method of discretization allows us to derive a number of interesting results based on finite dimensional optimization theory, namely, Karush-Kuhn-Tucker conditions of optimality and weak and strong duality. A number of examples are provided to illustrate the theory.
Keywords: Continuous time optimization; Discrete approximation; Linear Quadratic problems; Strict convexity